P665 Rapid sequence typing for antimicrobial resistance surveillance in neisseria gonorrhoeae using whole genome sequencing. (14th July 2019) - Phillips, Laura; Witney, Adam; Izquierdo-Carrasco, Fernando; Zhou, Liqing; Mayes, Simon; Laing, Kenneth; Tariq Sadiq, S
Abstract : Background: The Neisseria gonorrhoeae (NG) genome changes by ∼4 single nucleotide polymorphisms (SNP) per genome per year, information which is considered when predicting sexual networks using next generation sequencing to type circulating gonococcal strains. Oxford Nanopore Technologies' MinION provides opportunities for rapid "run-until" sequencing until a target coverage is achieved. We assessed MinION capacity to rapidly predict NG whole-genome strain type, from patients attending a London sexual health clinic, as an aid to rapid turn-around antimicrobial resistance (AMR) surveillance. Methods: One-directional MinION sequencing using bar-coded DNA library preparations from 44 well characterised NG isolates, prospectively collected from clinic, were run on MinION flow cells (version R9.2; three per flow cell) and Illumina MiSeq platform as a comparator. To determine shortest run-time to accurately predict strain type, MinION sequences at various time points and genome coverages were placed on a phylogenetic tree consisting of the same isolates sequenced on the MiSeq platform, clustered with a large European NG reference collection (Euro-GASP). Results: Total library preparation time was approximately one hour per flow cell. Whole genome coverage for MinION sequences varied per isolate as sequencing proceeded at different rates. In 44 isolates, 90 minutes of MinION sequencing produced a median coverage of 21-fold, and was sufficient for 30/44(68%) isolates to achieve <4 SNP differences compared to the corresponding MiSeq sequence. Estimated median SNP distance between the platforms at 90 minutes (of MinION sequencing) was 1.9 SNPs (IQR: 0.4–5.9). Conclusion: MinION sequencing enabled the placement of the majority of NG sequences onto the correct location on a reference tree after 90 minutes of sequencing, suggesting that such a method, particularly with newer iterations of the technology and library preparation protocols, might support early identification of sexual networks that support transmission, as well NG AMR surveillance. Disclosure: No significant relationships.